Analisis Implementasi Database Management System ( DBMS ) Dalam Mendukung Sistem Informasi Manajemen Pada Organisasi - Ferdi Akbar; Nuh Yabest Sinaga; Muhammad Rizal (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2026)
The development of information technology has encouraged organizations to manage data more effectively and in an integrated manner. In practice, many organizations still face various problems in data management, such as unstructured data, data duplication, slow information retrieval processes, and the risk of data loss. These conditions can affect the effectiveness of management information systems in supporting organizational activities and decision-making processes. This study aims to analyze the implementation of Database Management System (DBMS) in supporting management information systems within organizations. The study used a qualitative method with a literature study approach by collecting data from journals, books, scientific articles, and other relevant academic sources. The results, show that the implementation of DBMS plays an important role in improving data management efficiency, accelerating information access, increasing data accuracy, and supporting organizational data security. In addition, DBMS also assists management in decision-making processes because information can be obtained more quickly and systematically. However, the implementation of DBMS still faces several challenges, such as limited human resources, implementation costs, and data security risks. Therefore, organizations need to improve technological readiness, human resource quality, and security systems so that DBMS implementation can run optimally in supporting management information systems